2020
DOI: 10.1080/15257770.2020.1825733
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma nucleotide metabolites and amino acids pattern in patients with binge eating disorder and obesity

Abstract: Binge eating disorder (BED) increasingly affects population, but the mechanisms of the disease and its biomarkers are not well characterized. Recently, plasma purines, pyrimidines, amino acid and nicotinamide metabolites profiling attracted attention in studies on pathology and biomarkers of mental disorders but has not been adequately studied in BED. Blood and plasma samples were taken from patients with adult obese with BED (n ¼ 20) and control adult obese without BED (n ¼ 17). Plasma samples were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Glutamic acid is the most abundant amino acid in the human body, which provides energy for cell metabolism. It is also the hub of the transformation of purine, pyrimidine, amino sugar, and other amino acids in the body [47,48]. In addition to this, glutamine also participates in the immune response [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid is the most abundant amino acid in the human body, which provides energy for cell metabolism. It is also the hub of the transformation of purine, pyrimidine, amino sugar, and other amino acids in the body [47,48]. In addition to this, glutamine also participates in the immune response [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Our results aligned with previous studies showing associations between plasma and serum metabolomics data and metabolic outcomes. Epidemiological studies have suggested that levels of nucleotide metabolites are altered in obese adult populations [ 61 , 62 ] and could play a role in adipocyte functioning [ 63-65 ]. Plasma levels of nucleosides—pyrimidines and purines—were also found to be dysregulated in relation to obesity in children [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The information which pertains to the proper transcription of proteins is stored in the form of nitrogenous bases, the four most recognized being adenine, thymine, cytosine, and guanine (G). In addition to these nucleobases functioning as the genetic code of organisms, they also have several metabolic functions in extracellular signaling pathways [4,5]. Any changes made to the arrangement of the four nitrogenous bases or harm caused to them can potentially modify the sequence of the protein it transcribes, and hence, it may change the structure of the organism as well as trigger the emergence of specific illnesses [6].…”
Section: Introductionmentioning
confidence: 99%